Evaluasi Unjuk Kerja Alat Spektrofotometer UV-Vis Menggunakan Holmium Oksida dan Kalium Dikromat - Thorikul Huda; Cecep Sa'bana Rahmatillah; Yusuf Habibi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2011)
The Evaluation of Hitachi U 2010 UV-Vis Spectrophometer performance using holmium glass from Starna reference materials and potassium dichromate has been done. The aim of investigation with holmium glass was to known wavelength work region at ultra violet and visible area, potassium dichromate solution used to known photometric performance of UV-Vis spectrophotometer. The result of investigation used holmium glass showed wavelength peak at 241, 278, 287, 333, 360, 418, 445, 453, 459, 536 and 637 nm regions, wich it is similar with reference material. The determination of photometric resulted by absorbance value measurement at 235, 275, 313 and 350 nm were 0,746; 0,860; 0,294; 0,641 respectively. The result of wavelength and photometric investigation showed that Hitachi U 2010 spectrophotometer was proper to done and suitable with SR 03 KAN reference. Keywords: UV-Vis Spectrophometer, holmium glass, potassium dichromate, wavelength,